Alma y Como Obtuvo Su Nombre - Martinez-Neal, Juana (Somerville, Massachusetts : Candlewick Press, 2018)
When Alma Sofia Esperanza José Pura Candela asks her father why she has so many names, she hears the story of her name and learns about her grandparents.
Keywords: Families -- Juvenile fiction; Names, Personal -- Juvenile fiction; Hispanic Americans -- Juvenile fiction; Families -- Fiction; Names, Personal -- Fiction; JUVENILE FICTION -- Family; JUVENILE FICTION -- People & Places; JUVENILE FICTION -- Social Themes; Families; Hispanic Americans; Names, Personal; Picture books; Fiction; Juvenile works; Picture books; Picture books